2018
DOI: 10.1109/jbhi.2017.2708041
|View full text |Cite
|
Sign up to set email alerts
|

Self-Powered Multiparameter Health Sensor

Abstract: Wearable health sensors are about to change our health system. While several technological improvements have been presented to enhance performance and energy-efficiency, battery runtime is still a critical concern for practical use of wearable biomedical sensor systems. The runtime limitation is directly related to the battery size, which is another concern regarding practicality and customer acceptance. We introduced ULPSEK-Ultra-Low-Power Sensor Evaluation Kit-for evaluation of biomedical sensors and monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Despite numerous advances, battery runtime remains a critical limitation for the practical use of wearable sensors. Tobola et al described a “self-powered” sensor platform that incorporates an efficient body heat harvester 10 . Coronary heart disease is a leading cause ofpremature death worldwide, and there is a growing demand for a reliable system to detect critical cardiac abnormalities that lead to sudden death.…”
Section: Resultsmentioning
confidence: 99%
“…Despite numerous advances, battery runtime remains a critical limitation for the practical use of wearable sensors. Tobola et al described a “self-powered” sensor platform that incorporates an efficient body heat harvester 10 . Coronary heart disease is a leading cause ofpremature death worldwide, and there is a growing demand for a reliable system to detect critical cardiac abnormalities that lead to sudden death.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, by integrating the vital sign monitoring module into the system, other physiological signals such as the ECG, temperature, and respiration can be acquired on-demand. This ability to acquire raw PPG signals from multiple sites and at multiple wavelengths along with other physiological signals is a distinct advantage over the integrated solutions described for instance in [20]- [25]. Another example of the system's flexibility is the newly developed fiber optic TIA module that connects with traditional PPG sensors and/or fiber optic sensors [29].…”
Section: B Preliminary Evaluationmentioning
confidence: 99%
“…Hence, in the absence of a multiwavelength PPG system that can produce raw PPG signals and other physiological signals on-demand, researchers have resolved in custom building their own research systems. One of the many examples of such systems is the Ultra-Low-Power Sensor Evaluation Kit developed by Tobola et al [20] to measure ECG, respiration, motion, body temperature, and PPG. Other examples of such systems include [21]- [23].…”
Section: Introductionmentioning
confidence: 99%
“…In [26], Tobola et al developed an Ultra-Low Power Sensor Evaluation Kit (ULPSEK) for designing modulated, ultra-low power sensors, to be used together with a web-based battery runtime calculator. In [15], Tobola demonstrated that ULPSEK could be powered through 2 harvested body heat using a thermoelectric (TE) harvester with an average output power of 171 µW. Such studies are important towards understanding the power flow in autonomous self-sustained health monitoring devices.…”
Section: Introductionmentioning
confidence: 99%